Penggunaan Token Economic untuk Mengurangi Perilaku Agrsif pada Anak dengan Gangguan Intelektual - Indah Saroha; Marlina Marlina (Jurnal Penelitian Pendidikan Khusus, 2018)
This article contains the effectiveness of economic tokens in reducing aggressive behavior in mild mental retardation children, the aim is to reduce aggressive behavior in children by giving intervention in the form of behavior modification with economic tokens. This research is an experimental research in the form of single subject research with the design of A-B-A research. The subject of the research was a mild mental retardant child of grade VIII of the junior high school in SLB N 1 Harau. Data collection techniques in the form of observation or direct observation and data collection tools using recording of events using data collection instruments in the form of frequency, which means researchers calculate how many times the target behavior appears within 60 minutes. Data were analyzed using graphic visual data analysis techniques. Based on the results of the analysis in conditions and conditions, it was stated that the disturbing behavior of friends in children decreased and had a positive impact, after being given intervention using economic tokens. From the results of the study in getting aggressive behavior in children has decreased which means that proven economic tokens are effective in reducing aggressive behavior in children with mild mental retardation.